Will the Need‐Based Planning of Health Human Resources Currently Undertaken in Several Countries Lead to Excess Supply and Inefficiency? A Comment on Basu and Pak. (13th June 2016) - Birch, Stephen; Tomblin Murphy, Gail; MacKenzie, Adrian; Whittaker, William; Mason, Thomas
Abstract: Basu and Pak (2014) argue that need‐based workforce planning models would not maximize social welfare, and use of need‐based models would result in inefficiency. They propose that planning be based on service utilization to incorporate preferences or other socioeconomic factors. We show that the analysis is based on inappropriate considerations of the nature of healthcare demand, a misrepresentation of need‐based approaches and misunderstanding publicly funded healthcare system objectives. We explain how current levels of utilization emerge from workload and income interests of providers that underlie utilization‐based models and are incompatible with public goals of maximizing health gains. Copyright © 2016 John Wiley & Sons, Ltd.